AGRICULTURAL PRODUCTION IN DAGESTAN IN THE PERIOD OF THE GREAT PATRIOTIC WAR - Iskenderov, G A (History, Archeology and Ethnography of the Caucasus, 2015)
On the basis of new archival documentary material, information resources of historical press the author of the article considers the question of labor activity of agricultural people in the development of agricultural productivity in the difficult conditions of the Great Patriotic War.The author emphasizes that solving the problems of the organization of a gricultural productivity, reconstructing the economy of the collective farms and state agricultural enterprises (state farms) with regard to military conditions, the state authorities faced great difficulties: staffing problem, reduction of leading personnel and farm machinery operators, reduction of material and technical supply, increased intensity of work. In some farms there were fundamental changes in the organization of labor that resulted in the high rates of agronomic work, effective economic indicators in the development of production.
Keywords: collective farmers; production; cultivated areas; productivity; crops; food reserve; animal breeding; plant growing; wine growing; fruit growing.